Tjon Lines and Scaling Limit in Four-Body Systems - Tomio, Lauro [UNESP]; Delfino, A.; Frederico, T.; Hadizadeh, M. R. [UNESP]; Yamashita, Marcelo Takeshi [UNESP] (Springer Nature, 2013)
The fixed-slope correlation between tetramer and trimer binding energies, observed by Tjon in the context of nuclear physics, is mainly a manifestation of the dominance of the two-nucleon force in the nuclear potential, which makes the four-body scale on the order of the three-body one. In a more general four-boson case, the correlation between tetramer and trimer binding energies has a non-fixed slope, which expresses the dependence on the new scale. The associated scaling function generates a family of Tjon lines. This conclusion relies on a recent study with weakly-bound four identical bosons, within a renormalized zero-range Faddeev-Yakubovsky formalism. © 2012 Springer-Verlag.